Climate Change and Its Impacts on Flooding In Accra-Greater Accra Metropolitan Assembly - Sanquah, Isaac Odoi (2013)
A Thesis submitted to the School of Graduate studies, Kwame Nkrumah University of Science and Technology in Partial fulfillment of the requirement for the degree of Master of Science in Water Resources Engineering and Management.